Pembelajaran Mata Pelajaran Pendidikan Agama Islam Multikultural Dalam Membangun Profil Pelajar Pancasila - Wahyudi, Eko (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
The project to strengthen the profile of Pancasila students should be integrated into various activities and a conducive school culture. There are three ways to implement a holistic, comprehensive and integrated Pancasila student profile in learning, namely the Pancasila student profile project becomes subject matter in extracurricular activities, becomes a means of conducting learning experiences, and becomes a project in curricular activities. To design strategies for multicultural and ethnic relations in schools, it can be divided into two, namely personal experience and teaching carried out by teachers. The forms of teaching are as follows: first, teachers must be aware of students' ethnic diversity, they cannot educate them, second, curriculum and teaching materials should reflect ethnic diversity and third, curriculum materials are written in different regional/ethnic languages. Various breakthroughs and innovations in multicultural PAI learning will be able to make students have the character of a Pancasila student profile. Students' awareness will be formed indirectly so that over time they will grow into Pancasila students with Indonesian integrity.